Effect of growth hormone treatment on the adult height of children with chronic renal failure - Haffner, Dieter; Schaefer, Franz; Nissel, Richard; Wühl, Elke; Tönshoff, Burkhard; Mehls, Otto (The New England journal of medicine, 2000)
Children with chronic renal failure are at high risk for growth retardation and decreased adult height.1 Therapy with recombinant human growth hormone increases the growth rate and improves the standardized height (height expressed as the number of standard deviations from normal height) in prepubertal children with chronic renal failure.2,3 However, whether the final height is improved by this treatment is unknown. In children with growth hormone deficiency or idiopathic short stature, it has been suspected that growth hormone accelerates the onset or progression of puberty, thereby neutralizing the effect of any treatment-induced acceleration of prepubertal growth on adult height. . . .